The Impact of Intangible Assets on Capital Structure in Asia - Dudney, Donna; Harris, Chris; Li, Zhe; Morillon, Thibaut (Journal of Accounting and Finance, 2024)
Past studies find evidence that the level of intangible assets is positively related to corporate borrowing in the United States. This paper explores the relationship between intangible assets and capital structure for Asian countries. We identify a positive relationship between intangible asset investment and debt levels throughout Asia. Unlike in the United States, this positive relationship appears to be significant for non-Goodwill and Goodwill intangible assets. Further, we find that the magnitude of this relationship is significantly greater for developed Asian countries than for developing ones. We explore explanations for this difference related to firm size, firm age, cash flow volatility, and a firm’s likelihood to default on its debt.